Pengaruh Kurs dan Suku Bunga Bank Indonesia terhadap Dana Pihak Ketiga di Bankaltimtara Periode 2016-2018 - Khairil Akbar; Marwanto Marwanto; Reselia Situmorang (Jurnal EKSIS, 2022)
This research aims to determine the variables that affect the third party funds during the period of January 2016 to December 2018. The analysis of the research included the multiple regression analysis, descriptive analysis test, classical assumption test, and also the hypothesis testing. The rest results partially show that exchange rate (0,002) had a positive and significant effect on third party funds and BI Rate (0,073) had a positive and no significant effect. While the exchange rate and BI rate (8,590) had a positive and significant effect on the third party funds Regional Banking of East Kalimantan and North Kalimantan or Bankaltimtara.